Maisy makes gingerbread - Cousins, Lucy. (Cambridge, Mass. : Candlewick Press, 1999)
Maisy the mouse makes gingerbread cookies and shares them with her friends Charley and Tallulah.
Keywords: Baking -- Juvenile fiction; Cookies -- Fiction; Baking -- Fiction; Mice -- Fiction